The Effectiveness of The Malaria Cadres on Drug Intake Supervision, The Use of Mosquito Net and Environmental Modification on Malaria Sufferers at Malaria Endemic Area of Public Health Center of Waipukang, Lembata District, Nusa Tenggara Timur Province, Indonesia - Ragu Harming Kristina; Sri Subekti; Yoes Prijatna Dachlan; Santi Martini (Health Notions, 2017)
Malaria was a disease that caused many mortalities in developing countries. In solving this problem, it was needed a focused and directed mentoring continuously. This study aimed to determine the effectiveness of malaria cadres on drug intake supervision, the use of mosquito net and environmental modification on malaria sufferers at Public Health Center of Waipukang. This research was analytic observational research with cross sectional study design. The results showed that the average knowledge of malaria cadres was still low. Malaria cadres in Public Health Center of Waipukang were less effective in monitoring the consuming of malaria drugs, mosquito nets usage, and environmental modification in their areas. Furthermore, there were 78% of people who used mosquito net properly and 54% of families obediently did environmental modification efforts. Keywords: Malaria, Malaria cadre, Drug intake supervision, Environmental development, Mosquito net